Narcystyczna ciężkość życia i „nieznośna lekkość bytu” w aspekcie pedagogiki współczesnej młodzieży - Ściupider-Młodkowska , Mirosława (Studia Edukacyjne, 2022)
The article aims to indicate the contradiction of lightness and heaviness that permeates the culture of narcissism and tangibly affects the lives of young people, becoming problematic for future generations. Questions: Does cultural narcissism determine contemporary young people’s attitudes full of contradictions, the antinomy of lightness and heaviness? If so, how does narcissism affect the understanding of community and relationships? The meeting places and relational spaces of young people, mediated by the media, spread the virus of adoration, self-admiration and privilege; this is a direct result of cultural narcissism. I observe this and many other determinants of dissociation resulting from the influence of the culture of egoism in the self-destructive attitudes and choices constructed by young people. Self-indulgence and adoration very often lead to a sense of emptiness, little worth and loneliness. This article will defend theses on visible dissociation in selected areas of youth’s existence. I will refer to the analyses of interviews with selected students conducted within the pilot research project on “Ego Addicts”. The background for the considerations is also examples from the life of characters from the prose of Milan Kundera; inspirational, they are both unbearably light and heavy. The narcissistic lightness of being can become a direction indicator for educators in diagnosing the heaviness, i.e. low value and loneliness and other dilemmas of youth.